Accidental Sewing Pin Ingestion by a Tailor: A Case Report and Literature Review - Stefan Stojkovic; Milica Bjelakovic; Milica Stojkovic Lalosevic; Milos Stulic; Nina Pejic; Nemanja Radivojevic; Nemanja Stojkovic; Jelena Martinov Nestorov; Djordje Culafic (Medicina, 2023)
Foreign body ingestion is a frequently encountered emergency in healthcare institutions. It mostly affects pediatric populations, although it can also affect adults with developmental delays, those with psychiatric diseases, drug abusers, and prisoners. Endoscopy is a diagnostic and treatment method for suspected foreign body ingestion. In this article, we discuss a 45-year-old tailor who swallowed a sewing pin while at work. The abdominal X-ray showed a needle-shaped metal shadow in the stomach region. During an upper endoscopy, it was discovered that a sewing pin with a sharp edge was stuck in the pylorus. The sewing pin was extracted endoscopically, and the patient was discharged the same day in good condition. Since the estimated risk of complications of foreign body ingestion in the adult population is about 35%, and the most common complications include impaction, laceration, bleeding, or perforation of the gastrointestinal wall, endoscopic or surgical removal is necessary. This also emphasizes the importance of a careful endoscopic evaluation of some at-risk occupations for foreign body ingestion with or without gastrointestinal complaints.